Effect of Carbon/Carbon Preform Density on the Microstructure and Properties of Mo2C Interlayer‐Modified Carbon/Carbon–Copper Composites for Sliding Contact Materials1. Issue 2 (14th July 2015) - Zhou, Wen Yan; Ran, Li Ping; Peng, Ke; Ge, Yi Cheng; Wu, Huang; Yi, Mao Zhong
Abstract : Carbon/carbon–copper(C/C‐Cu) composites were fabricated by pressure‐less infiltration of Cu into carbon/carbon (C/C) preforms modified with Mo2 C interlayer by a molten salt method. Cu filled the pores inside the Mo2 C‐modified preforms fully, and retained an interconnected net‐like distribution in the C/C‐Cu composites. The electrical resistivity and flexural strength increased, whereas impact toughness decreased with the increase of preform density. Fiber pull‐out and crack propagation along the interface contributed to the pseudo‐plastic behavior of the composites. The tribological performance was improved with the increase of preform density due to the better lubrication of transfer films. Abstract : C/C‐Cu composites are fabricated by pressure‐less infiltration of Cu into Mo2 C‐modified C/C preforms . With the increase of preform density, the electrical resistivity, flexural strength increases, impact toughness decreases, and tribological performance is improved due to the better lubrication of transfer films. Fiber pull‐out and crack propagation contributes to the pseudo‐plastic fracture.